2015
DOI: 10.1055/s-0035-1565250
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Algorithm and Results of Isolated Traumatic Axillary Nerve Injuries

Abstract: In patients with preserved triceps strength, a triceps branch of the radial nerve can be coapted directly to the axillary nerve in the absence of deltoid contraction following electrical stimulation. Functional improvements were seen in patients treated with neurolysis alone and in combination with nerve transfer, supporting the use of intraoperative axillary nerve stimulation to guide treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(43 reference statements)
0
4
0
2
Order By: Relevance
“…27 Surgical reconstruction of a closed axillary nerve injury via nerve graft or nerve transfer is recommended when there is no spontaneous recovery 3 to 6 months after the injury. 1, 5,24 Multiple studies have demonstrated that a triceps nerve to axillary nerve transfer leads to increased deltoid strength in both pediatric and adult populations with axillary nerve injury. 8,14,27,29 This surgery may increase shoulder endurance postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Surgical reconstruction of a closed axillary nerve injury via nerve graft or nerve transfer is recommended when there is no spontaneous recovery 3 to 6 months after the injury. 1, 5,24 Multiple studies have demonstrated that a triceps nerve to axillary nerve transfer leads to increased deltoid strength in both pediatric and adult populations with axillary nerve injury. 8,14,27,29 This surgery may increase shoulder endurance postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…At 3 months postinjury, the lack of spontaneous recovery (the absence motor units on electromyography [EMG]) is an indication for surgery. 4,5,24 By contrast, if the surgery is delayed and evidence of acute denervation (fibrillations or positive sharp waves on EMG) is no longer present, nerve transfers are less likely to be successful. 25 Additionally, a surgical decompression of the quadrangular space with step lengthening of the long head of the triceps tendon may relieve a conduction block in the axillary nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Chen et al reported transferring a triceps branch of the radial nerve to the axillary nerve in patients without deltoid function (but preserved triceps strength) and found that both the neurolysis alone and the nerve transfer groups had significant improvements in deltoid strength and shoulder abduction from a mean of 63 to 127 degrees. 15 When patients present outside the window for neurotization or fail to have shoulder function improvement after brachial plexus nerve reconstruction, tendon transfer is the initial reconstructive step. Few muscles are available after the injury for tendon transfer.…”
Section: Discussionmentioning
confidence: 99%
“…При порівнянні віддалених результатів пластики та невротизації аксилярного нерва значних розбіжностей виявлено не було. В обох випадках спостерігались добрі результати відновлення сили дельтоподібного м'яза у 80-86 % до М4-М4+, та у 57 % досягнуто М5 [1,3,5,7].…”
Section: îáãîâîðåííÿunclassified